The not-yet-conscious: protentional consciousness and the emergence of the new - Fuchs, Thomas (Phenomenology and the cognitive sciences, 2024)
Not only our conscious expectations, wishes and intentions are directed towards the future, but also pre- or unconscious tendencies, hunches and anticipations. Using a term of Ernst Bloch, they can be summarized as the not-yet-conscious. This not-yet-conscious mostly unfolds spontaneously and without plan; it is not directly anticipated or aimed at, but rather comes to awareness in such a way that the subject is, as it were, surprised by itself. Thus it gives rise to phenomena such as the striking, the coincidental, the new, and the improvised, which are particularly important for understanding creative and therapeutic processes. The paper aims at providing a general phenomenological framework for the understanding of not-yet-conscious dynamics and their unfolding in different contexts. To this end, the structure of the not-yet-conscious is examined in light of protention, in which the phenomenon is fundamentally to be located. I propose to describe the general structure of protention as a future-directed horizon of graded probabilities, i.e., as a “protentional cone”. This cone is fed by current experiences and bodily tendencies and is focused to varying degrees by attention. This results in either more focused or rather defocused states of anticipation, the latter giving space to the not-yet-conscious as a meaning “in statu nascendi”. On this basis, selected manifestations of the not-yet-conscious are analyzed, including extemporaneous speech, artistic improvisation and creativity, bodily meaning implicates, decision-making, and meaningful coincidence.